Alpha-Synuclein Pathology and the Role of the Microbiota in Parkinson’s Disease - Fitzgerald, Emily; Murphy, Sarah; Martinson, Holly A. (Frontiers in Neuroscience, 2019)
There is a principle in science, known as Occam’s razor, that says the correct solution is usually the one with the simplest explanation. The microbiota-gut-brain axis, an interdependent series of communication loops between the enteric nervous system, the microbiota, the gut, and the brain, offers important insight into how changes in our gut affect distant organs like our brains. The inherent complexity of this axis with the crosstalk between the immune system, inflammatory states, and the thousands of bacteria, viral, and fungal species that together make up the microbiota make studying the interactions that govern this axis difficult and far from parsimonious. It is becoming increasingly clear that the microbiota is integral to this axis. Disruption of the healthy flora, a phenomenon collectively referred to as dysbiosis, has been implicated as a driver for several diseases such as irritable bowel syndrome, rheumatoid arthritis, obesity, diabetes, liver disease, and neurological disorders such as depression, anxiety, and Parkinson’s disease (PD). Teasing apart these complex interactions as they pertain to PD is critical for our understanding of this debilitating disease, but more importantly, for the development of future treatments. So far, treatments have been unable to stop this neurodegenerative disease, succeeding only in briefly dampening symptoms and buying patients time before the inevitable loss of function ensues. Given that the 10-year prognosis for death or life-limiting disability with someone diagnosed with PD is upwards of 80%, there is a desperate need for curative treatments that go beyond symptom management. If PD does begin in the periphery with bidirectional communication between the microbiota and the immune system, as recent literature suggests, there is an exciting possibility that progression could be stopped before it reaches the brain. This systematic review assesses the current literature surrounding the role of the microbiota in the pathogenesis of alpha-synucleinopathies and explores the hypothesis that alpha-synuclein folding is modulated by the microbiota. Furthermore, we discuss how changes in the gut environment can lead to pathology and outline the implications that advances in understanding the interactions between host and microbiota will have on future research and the development of potential biomarkers.